2005
DOI: 10.5739/isfp.2005.449
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Linear Controllers for a Hydraulic Servo System

Abstract: In many hydraulic control applications, classic linear controllers are still employed, although there exist a number of number of nonlinear control methods, which may be better suited for handling the intrensic non-linearities often found in hydraulic systems. The focus of this paper is therefore on comparing different linear controllers, based on both simulation and experimental results, to determine what is obtainable when applying standard linear controllers to a hydraulic SISO servo system. The paper furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Andersen et al proposed a forklift with the power system of a battery-EM-hydraulic pump. The test results showed that the energy regeneration efficiency could be up to 40% [17,18]. The efficiency of PERS was increased by 18% in the low speed mode and 30% in the high speed mode.…”
Section: Introductionmentioning
confidence: 99%
“…Andersen et al proposed a forklift with the power system of a battery-EM-hydraulic pump. The test results showed that the energy regeneration efficiency could be up to 40% [17,18]. The efficiency of PERS was increased by 18% in the low speed mode and 30% in the high speed mode.…”
Section: Introductionmentioning
confidence: 99%
“…Active damping of hydraulic systems based on pressure feedback has been around for decades [13]. It is also used in mobile machine structures, large-inertia load device movement, hydraulic servo controller design, hydro-dynamic control, and energy-saving active dampers [14][15][16][17][18]. The method of designing outlet throttle holes considering system dampness is also involved [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, research efforts have been directed toward meeting these requirements. Most of these studies have been based on the linear control theory [2][3][4][5]. However, in such works, some important dynamic information may be lost when the hydraulic servo system is linearized around some operating point during the design.…”
Section: Introductionmentioning
confidence: 99%